다물체 동역학을 이용한 양광펌프 거치대의 유압 실린더 설계 및 구조 안전성 평가 - 오재원(Jae-Won Oh); 민천홍(Cheon-Hong Min); 이창호(Chang-Ho Lee); 홍섭(Sup Hong); 김형우(Hyung-Woo Kim); 여태경(Tae-Kyung Yeu); 배대성(Dae-Sung Bae) (Han-guk haeyang gonghak hoeji (Online), 2015)
When a deep-seabed lifting pump is kept this device has bending and deformation in the axis due to its long length(8m). These influences can be caused a breakdown. Therefore, a mounting must be developed to keep the lifting pump safe. This paper discusses the hydraulic cylinder design of the lifting pump and structural safety estimation of the mounting using SBD(simulation-based design). The multi-body dynamic simulation method is used, which has been used in the automotive, structural, ship building, and robotics industries. In this study, the position and diameter of the hydraulic cylinder were determined based on the results of the strokes and buckling loads for the design positions of the hydraulic cylinder. A structural dynamic model of the mounting system was constructed using the determined design values, and the structural safety was evaluated using this dynamic model. According to these results, this system has a sufficient safety factor to manufacture.